Pluralism and Identity, Studies in Ritual Behaviour. - Platvoet; van der Toorn (Editors) (Numen Book Series, 1995)
The subject of this book is ritual behaviour, in particular of groups with a distinctive religious, ethnic or other identity which use rituals to pursue strategic ends ad intra and ad extra . Five essays offer theoretical perspectives on ritual in plural and pluralist societies, on similarity and demarcation, on the negative case of the Australian Aboriginals, on Brazilian religious pluralism, and on Ghanaian churches in the Netherlands. Three essays describe the ritualization of the encounter, or confrontation, between religions in India (between Buddhists and Hindus, and between Hindus and Muslims), and in Yemen between Muslims and Jews. Four essays study the responses to internal religious plurality, in early Israel, on Java, in Indonesia, and in Spain and North Africa. One essay explores responses to external religious plurality. In the epilogue, the social nature of pluralism and identity is highlighted.